问题
解答题
数列{an}中,a1=a,an+1=can+1-c(n∈N*)a、c∈R,c≠0 (1)求证:a≠1时,{an-1}是等比数列,并求{an}通项公式. (2)设a=
(3)设a=
|
答案
(1)证明:∵an+1=can+1-c,∴an+1-1=c(an-1)
∴a≠1时,{an-1}等比数列.
∵a1-1=a-1,∴an-1=(a-1)cn-1,∴an=(a-1)cn-1+1
(2)由(1)可得an=-
(1 2
)n-1+1=-(1 2
)n+11 2
∴bn=n•(
)n1 2
∴Sn=1•
+2•(1 2
)2+…+n•(1 2
)n1 2
∴
Sn=1•(1 2
)2+2•(1 2
)3+…+(n-1)•(1 2
)n+n•(1 2
)n+11 2
两式相减可得
Sn=1 2
+(1 2
)2+(1 2
)3+…+(1 2
)n-n•(1 2
)n+1=1-1 2 n+2 2n+1
∴Sn=2-n+2 2n
(3)证明:Cn=4+
,5 (-4)n-1
dn=
=25×16n (16n-1)(16n+4)
<25×16n (16n)2+3×16n-4
<25×16n (16n)2 25 16n
∴Tn=d1+d2+…+dn<25(
+1 16
+1 162
+…+1 163
)=1 16n
=25×
(1-(1 16
)n)1 16 1- 1 16
(1-5 3
)<1 16n 5 3